Psychrophіlic methylotrophyc bacteria in Antarctic region biotopes - Romanovskaya, V.A.; Rokitko, P.V.; Tashirev, O.B.; Shilin, S.O.; Chernaya, N.A. (Український антарктичний журнал, 2006)
Search of methylotrophic bacteria has been carried out during time VIIth Ukranian Antarctic expedition (2003) at station «Academic Vernadsky». The psychrotolerant bacteria obligately using a methane have been found out in samples of mosses in an island part of Antarctic Region and in soil-plant samples. The quantity of methane oxidizing bacteria in samples from Antarctica (101–103 /g of the sample) was lower, than in samples from regions with a temperate climate (102–106 /g of the sample). The psychrotolerant bacteria of genus Methylobacterium facultatively using a methanol have been revealed in the silt of fresh and «Red» lakes, and also in soil-plant samples. Single psychrophilic strain which, probably is a new species of genus Methylobacterium was isolated at 10ºС from soil-plant sample of Antarctic Region. The majority of the collection mesophilic strains Methylobacterium isolated earlier from soils and plant phyllosphere from various regions of Ukraine is shown, that, also were capable to grow at 10ºС. It was shown, that strains Methylobacterium are not catalysts of process of formation of ice. Moreover, some from them are capable to reduce temperature of freezing of water (process of crystallization of ice at their presence began at temperature lower-13С), that is, naturally they have «antifreezing»effect on process of crystallization of ice. These properties of strains Methylobacterium may be very important in conditions of Antarctica for a survival both microbic, and plant forms. As a whole, psychrotolerant facultative methylotrophs and the obligate methane oxidizing bacteria revealed by us in various ecosystems of Antarctic Region, expand representation about a physiological diversity of these groups of bacteria, about their distribution to biosphere and the contribution to a global cycle of carbon.